ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP PARTISIPASI MASYARAKAT DALAM PEMELIHARAAN SALURAN DRAINASE DI KELURAHAN MANNURUKI KOTA MAKASSAR - Marzuki Dilla (Purifikasi, 2006)
This study was aimed to determine the influencing factors of the community participation towards the maintainance of drainage canal. The method was based on the analysis of environment knowledge, environmental attitude , level of education and income, using direct observation, document analysis, knowledge test, attitude scale, and inferential statistics. The research showed that the community participation to maintain the drainage is at the medium level, with a significant influence. The significance included: (1) enviroment knowledge to community participation (ry1 = 0,916), (2) environmental attitude to community participation (ry2 = 0,910), (3) education level to community participation (correlation ry3 = 0,913), (4) income to community participation (ry4 = 0,432), (5) influence of all independent variables to participation in drainage clean maintainance (ry1,2,3,4 = 0,947).